2004
DOI: 10.2337/diabetes.53.2007.s51
|View full text |Cite
|
Sign up to set email alerts
|

Aged Transgenic Mice With Increased Glucocorticoid Sensitivity in Pancreatic β-Cells Develop Diabetes

Abstract: Glucocorticoids are diabetogenic hormones because they decrease glucose uptake, increase hepatic glucose production, and inhibit insulin release. To study the long-term effects of increased glucocorticoid sensitivity in ␤-cells, we studied transgenic mice overexpressing the rat glucocorticoid receptor targeted to the ␤-cells using the rat insulin I promoter. Here we report that these mice developed hyperglycemia both in the fed and the overnight-fasted states at 12-15 months of age. Progression from impaired g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 35 publications
6
59
0
2
Order By: Relevance
“…66 Finally, aged transgenic mice that display increased sensitivity to glucocorticoids in pancreatic beta-cells develop diabetes. 67 These results can be relevant for humans -a recent study has shown that a polymorphism in the glucocorticoid receptor gene is associated with decreased sensitivity to glucocorticoids and decreased insulin and cholesterol levels in vivo. 68 A single nucleotide polymorphism on exon 2 of the glucocorticoid receptor gene is associated with increased sensitivity to glucocorticoids and obesity in nondiabetic subjects.…”
Section: A B C D E F G Hmentioning
confidence: 93%
“…66 Finally, aged transgenic mice that display increased sensitivity to glucocorticoids in pancreatic beta-cells develop diabetes. 67 These results can be relevant for humans -a recent study has shown that a polymorphism in the glucocorticoid receptor gene is associated with decreased sensitivity to glucocorticoids and decreased insulin and cholesterol levels in vivo. 68 A single nucleotide polymorphism on exon 2 of the glucocorticoid receptor gene is associated with increased sensitivity to glucocorticoids and obesity in nondiabetic subjects.…”
Section: A B C D E F G Hmentioning
confidence: 93%
“…Further evidence for the ability of GCs to suppress insulin output was obtained in vivo in experiments with mice overexpressing the GR in pancreatic β-cells. This genetic modification leads to decreased insulin secretion accompanied by reduced glucose tolerance in adult mice and hyperglycemia in aged mice [250,251]. In the latter case, enhanced α-adrenergic receptor signaling was reported in GRoverexpressing cells, a finding that has been linked to suppression of insulin release [251].…”
Section: Pancreatic β β β β-Cellsmentioning
confidence: 99%
“…When these transgenic mice aged, hyperglycaemia developed together with marked glucose intolerance and reduced in vivo and ex vivo GSIS. Remarkably, no change in b-cell apoptosis was observed in these mice (Davani et al 2004). This deterioration in GSIS was prevented by incubating islets with benextramine (a selective a2-adrenergic receptor antagonist), suggesting the involvement of adrenergic signals.…”
Section: Gc Treatment B-cell Dysfunction and Glucose Intolerancementioning
confidence: 99%
“…In an attempt to analyse whether GCs have any direct effects on b-cells in vivo independent of peripheral GC actions, a transgenic mice model that specifically overexpresses GR in these cells was generated (Delaunay et al 1997, Davani et al 2004. These mice were normoglycaemic, but displayed glucose intolerance associated with reduced insulin secretion during a glucose load (Delaunay et al 1997).…”
Section: Gc Treatment B-cell Dysfunction and Glucose Intolerancementioning
confidence: 99%